2011
DOI: 10.1002/etc.689
|View full text |Cite
|
Sign up to set email alerts
|

Joint toxicity of a pyrethroid insecticide, cypermethrin, and a heavy metal, lead, to the benthic invertebrate Chironomus dilutus

Abstract: Abstract-Insecticides and heavy metals are frequently detected in the environment, but few studies have assessed the joint toxicity of organic and inorganic contaminants. Joint toxicity of a pyrethroid insecticide, cypermethrin, and a heavy metal, Pb 2þ , was evaluated in the present study. An antagonistic toxic response was observed when the benthic invertebrate Chironomus dilutus was simultaneously exposed to the two contaminants in both water and sediment exposures. Pre-exposure bioassays with midges were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 35 publications
(59 reference statements)
0
12
0
Order By: Relevance
“…Elevated levels of heavy metals, especially lead, have been detected in sediment in Guangzhou urban waterways (Cheung et al, 2003). Mehler et al (2011c) noted an antagonistic interaction between cypermethrin and lead to C. dilutus, and deemed that the co-existence of lead in sediment might reduce cypermethrin toxicity to C. dilutus in some field sediments. So, antagonistic interactions between cypermethrin and lead might also be one of the reasons for the unexpectedly low toxicity to H. azteca in Chebei Creek sediments.…”
Section: Reduced Bioavailability and Toxicitymentioning
confidence: 99%
“…Elevated levels of heavy metals, especially lead, have been detected in sediment in Guangzhou urban waterways (Cheung et al, 2003). Mehler et al (2011c) noted an antagonistic interaction between cypermethrin and lead to C. dilutus, and deemed that the co-existence of lead in sediment might reduce cypermethrin toxicity to C. dilutus in some field sediments. So, antagonistic interactions between cypermethrin and lead might also be one of the reasons for the unexpectedly low toxicity to H. azteca in Chebei Creek sediments.…”
Section: Reduced Bioavailability and Toxicitymentioning
confidence: 99%
“…Another sediment sample collected from a drinking water reservoir in Conghua, Guangdong was used as a control sediment. A previous study (Mehler et al, 2011a) showed this control sediment was non-toxic to benthic organisms and contained limited contamination. Total sediment OC was measured using an Elementar Vario ELIII (Hanau, Germany) after removing the inorganic carbonates with 1 mol/l HCl.…”
Section: Sediment and Organismsmentioning
confidence: 86%
“…The extraction was repeated twice, and the combined extracts were filtered, solvent exchanged to 2 ml of dichloromethane, and cleaned with gel permeation chromatography (LabTech, Beijing, China) following the method described by Mehler et al (2011a). After cleanup, the eluents were concentrated, solvent exchanged to 0.5 ml of hexane and analyzed using GC/MS after the addition of 500 ng of internal standards.…”
Section: Sediment and Biota Extractionmentioning
confidence: 99%
“…When organisms were exposed to a mixture of chemicals, one constituent may affect the uptake, biotransformation, distribution and elimination of the others, and this would lead to joint interaction among chemicals and subsequently change toxicity (Belden and Lydy, 2000;Mehler et al, 2011). Thus, alteration in toxicokinetic parameters may serve as a good indicator for the mechanism of joint toxicity.…”
Section: Toxicokinetic Parameters Of Permethrinmentioning
confidence: 99%
“…On the contrary, alteration of toxicokinetics may also cause antagonism. Antagonistic interaction between permethrin and cadmium as well as cypermethrin and lead in C. dilutus was attributed to enhanced biotransformation of pyrethroids with the addition of metals (Chen et al, 2015;Mehler et al, 2011). Joint toxicity between chemicals may depend on their exposure levels (Banks et al, 2003).…”
Section: Introductionmentioning
confidence: 99%